TALAASH: CONVERSATIONAL IMPLICATURE LYING WITHIN - Ice Sariyati (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
This study was aimed to analyze the types of clause, characteristics of speech act, as well as the implied intents in conversational implicature. This research used descriptive qualitative method by analyzing document and sources of the data were taken from English subtitle of one Bollywood movie entitled Talaash. From the data analysis the findings showed that the clause type of conversational implicature in one Bollywood movie entitled Talaash was dominated by declarative one and its characteristic of speech act was making a statement. On the other hand, the type of clause least found was exclamative one and its characteristic of speech act was making an exclamatory statement. Besides, the clause of declarative, closed interrogative, imperative and exclamative types were in line and not in line with their own characteristic of speech act. Meanwhile, the clause of open interrogative type was only found in line with its own characteristic of speech act. Based on the results of data analysis and its discussion, it can be drawn on conclusion that the conversational implicature is often found in the text of a literary work, especially in movie dialogue. It means that the readers or the audiences should understand it well in order not to misunderstand the conveyed meaning or intents so they can enjoy it with satisfaction.